İbn Teymiyye'nin Mecmuu'l-Fetâvâ adlı eserinde Yahudilik ve Hıristiyanlık - İsakov, Asilbek (My University, 2019)
İbn Teymiyye'nin Mecmûu'l-Fetâvâ adlı eserinde tarih boyunca Yahudilik ve Hıristiyanlığı çok sert bir dille eleştirdiği konular yer almaktadır. Bu tez çalışmasında ise sadece İbn Teymiyye'nin Mecmûu'l-Fetâvâ adlı eseri değil el-Cevâbü's-Sahîh li Men Beddele Dîne'l-Mesîh ve er-Risâletü'l-Kıbrısiyye adlı eserlerinden de istifade edilerek Yahudilik ve Hıristiyanlığın öncelikle kutsal kitab'a nasıl sahip çıktıkları, kendilerine gönderilen peygamberlere nasıl icabet ettikleri ve kendilerine vahyedilen kitapta olmayan idddiaları işlenmektedir.

In today's history of religions, Judaism and Christianity come in front of the religions, which have an important position in history and in cultures of the human community. Islam followed the path and sources of these two religions, while providing some information about how the Jews and Christians hold on to the Judaism and Christianity, it also stated that heralded itself with the good news in these two religions.As soon as the Islam came into being, it has developed in a short period of time and it has contained the members of the two religions in its geography and their religion was not intervened by muslims. But the Islam or the newly revealing Qur'an as mentioned them, alleged by Muslims that they had changed their religion to a very different form than they were sent by Allah. One of the Islamic scholar who wrote books regarding this matter was great Islamic scholar Taqī al-Dîn Ahmad ibn Taymiyyah. Ibn Taymiyyah is one of the very important scholar with great personality and also referred himself with the distinctive character in Islamic world who lived seven to eight centuries before our age and left various valuable works in Islam and other religions. In this study, we try to work on subject as we mentioned Judaism and Christianity in the content of the Ibn Taymiyyah's work 'Majmau'l-Fatawa' (Great Compilation of Fatwa), although try to work on his work 'al-Jawāb al-Ṣaḥīḥ li-man Baddala dīn al-Masīh' (The Correct Reply to those who Altered Christ's Religion), which was written with the heaviest criticism regarding the Ahl al-Kitāb (People of the Book).
Keywords: Christianity; Hıristiyanlık; History; Islamic interpretations; İbn Taymiyya; İbn Teymiyye; İsa Mesih; İslami yorumlar; Jesus Christ; Jews; Judaism; Majma ul Fatawa (Great Compilation of Fatawa); Mecmûu'l-Fetâvâ; Musevilik; Tarih; Yahudiler; Yahudilik